Evaluating the carbon leakage effect on cement sector under different climate policies. (1st October 2017) - Allevi, Elisabetta; Oggioni, Giorgia; Riccardi, Rossana; Rocco, Marco
Abstract: The European-Union Emissions Trading System (EU-ETS) is a cap and trade scheme that requires the industries participating in the program to obtain allowances to cover their carbon emissions. Energy Intensive Industries claim that this system puts their European plants at an economics disadvantage compared to facilities located outside the EU. As a direct consequence, industries may relocate their production activities in unregulated countries, leading to the so-called carbon leakage effect. In order to curb this effect, several policies have been devised, including grandfathering of CO2 allowances and border tax adjustment. This paper investigates the impact of these two policies on the cement sector, with a particular focus on the Italian market, particularly prone to carbon leakage. The analysis is based on an oligopolistic partial equilibrium model with a detailed technological representation of the market. The model is a Generalized Nash Equilibrium Problem that accounts for the interactions of cement companies. Simulations show that neither the grandfathering nor the border tax adjustment fully solve the carbon leakage problem because cement companies modify their cement and clinker trade strategies according to the measure applied in order to avoid or reduce their carbon costs. Highlights: We analyze the carbon leakage effect on the European cement sector under different pollution prevention measures. We consider coastal and inland plants separately. Coastal plants are more exposed to carbon leakage. Free permit allocation (FA) and border tax adjustment (BTA) are partial remedies. With FA, cement companies relocate clinker production in unregulated areas. With BTA on clinker, companies import directly cement from no ETS areas.